The principal's influence on the novice teacher's professional development in literacy instruction. Issue 2 (15th March 2018) - Kindall, Heather D.; Crowe, Tracey; Elsass, Angela
Abstract: Effective teachers and principals, who are viewed as their building's curriculum leader, are of vital importance to the literacy success of elementary-age students. This article will explore the influences of school leadership and professional development which teachers say can positively or negatively impact their ability to effectively teach literacy in the elementary grades. Novice teachers in this study reported that the knowledge their principal held in the field of literacy made a significant impact on their ability to effectively deliver literacy instruction. Findings have implications for the effective design of continued professional development for elementary teachers in order to optimize literacy outcomes for students.